Gestão de riscos como ferramenta de governança: um estudo de caso com três universidades públicas federais - Santos, Adilson Miranda dos (Universidade Federal de São Carlos, 2024)
The present study aimed to investigate the implementation of risk management in federal public universities. It is a research study that, based on the theoretical framework, addresses the evolution of public governance and risk management, particularly in the context of federal public universities. It is understood that public governance involves evaluating, directing, and monitoring management to deliver a good or service of interest to society. For this purpose, risk management is shown to be a fundamental governance tool, integrating into decision-making so that senior management can identify and manage uncertainties and risks in advance to achieve institutional objectives. The central issue of the research was to understand how universities are dealing with the process of implementing risk management. To investigate this issue, a study of polar cases was conducted, focusing on identifying the actions taken and the difficulties encountered. The selection of institutions initially considered the evaluation of federal public universities regarding their organizational risk management capacity, according to the Integrated Profile of Organizational Governance and Public Management prepared by the Federal Court of Accounts. Subsequently, based on the application of specific criteria, the chosen universities were the Federal University of Lavras, the Federal University of Vales do Jequitinhonha and Mucuri, and the Federal University of Rio de Janeiro. Data collection was carried out through semi-structured interviews with participants holding management positions in the selected universities. The results identified difficulties that have prevented the universities from effectively implementing risk management. This may explain why in some universities, risk management is carried out merely as a formality. The study also identified best practices and suggestions that, if adopted, can assist in the effective implementation of risk management and the overcoming of identified obstacles.
Risk management as a governance tool: a case study of three federal public universities
Keywords: Governança pública; Gestão pública; Gestão de riscos; Administração pública; Universidade federal; Public governance; Public management; Risk management; Public administration; Federal university; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA